Retirement Wealth Adequacy Estimation Based on Income Group Classification: A Case Study in Malaysia - A. A. Adnan; R. I. Alaudin; A. M. Yaakob; N. Ismail (Финансы: теория и практика, 2023)
The inadequacy of retirement wealth can significantly impact a country’s social support system. The increase of the size of the elderly population in line with the constant growth of life expectancy among Malaysians has triggered a question, are there enough resources to cover needs in retirement years? The main objective of this study is to estimate the retirement income adequacy of future retirees under a defined contribution (DC) plan, which is the Employee Provident Fund (EPF). The projection of retirement income adequacy uses cross-sectional data from the Malaysian Household Income Survey (HIS) 2014, based on 14,169 sample households. The households are categorized according to three different income groups, including Top 20% (T20), Middle 40% (M40) and Bottom 40% (B 40). In addition, this research also investigates the demographic and socio-economic determinants of retirement wealth adequacy using OLS and logistic regression. The result shows that 26% of households in the sample have inadequate retirement income, especially households in the B 40 group.